If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3+6x=5x-13
We simplify the equation to the form, which is simple to understand
-3+6x=5x-13
We move all terms containing x to the left and all other terms to the right.
+6x-5x=-13+3
We simplify left and right side of the equation.
+1x=-10
We divide both sides of the equation by 1 to get x.
x=-10
| 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 | | -3+6x=5x-13 | | 9(x-8)+28=9x-44 | | 6/7*7/8 | | 27+2x+5+3x-4=180 | | -9(9+u)-2u=-10 | | 3t+4+t=6 | | (3t^4)(-2t)(5t^6)=x | | -9(9+u)-2u=-10 | | -3+6x=5x-13 | | 6/7*7/8 | | 6/7*7/8 | | 5x+10y=-20findx | | x=56-3x | | 3t+4+t=6 | | 25-2x=-(-6+7) | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | x=56-3x | | 6w-5= | | 0.4x=2.40 |